Ascl1 (Mash1) defines cells with long-term neurogenic potential in subgranular and subventricular zones in adult mouse brain. - Euiseok J Kim; Jessica L Ables; Lauren K Dickel; Amelia J Eisch; Jane E Johnson (PLoS ONE)
Ascl1 (Mash1) is a bHLH transcription factor essential for neural differentiation during embryogenesis but its role in adult neurogenesis is less clear. Here we show that in the adult brain Ascl1 is dynamically expressed during neurogenesis in the dentate gyrus subgranular zone (SGZ) and more rostral subventricular zone (SVZ). Specifically, we find Ascl1 levels low in SGZ Type-1 cells and SVZ B cells but increasing as the cells transition to intermediate progenitor stages. In vivo genetic lineage tracing with a tamoxifen (TAM) inducible Ascl1CreERT2 knock-in mouse strain shows that Ascl1 lineage cells continuously generate new neurons over extended periods of time. There is a regionally-specific difference in neuron generation, with mice given TAM at postnatal day 50 showing new dentate gyrus neurons through 30 days post-TAM, but showing new olfactory bulb neurons even 180 days post-TAM. These results show that Ascl1 is not restricted to transit amplifying populations but is also found in a subset of neural stem cells with long-term neurogenic potential in the adult brain.